2012
DOI: 10.1186/1744-8069-8-61
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Dynamics of Re-Innervation and Hyperinnervation Patterns by Uninjured CGRP Fibers in the Rat Foot Sole Epidermis after Nerve Injury

Abstract: The epidermis is innervated by fine nerve endings that are important in mediating nociceptive stimuli. However, their precise role in neuropathic pain is still controversial. Here, we have studied the role of epidermal peptidergic nociceptive fibers that are located adjacent to injured fibers in a rat model of neuropathic pain. Using the Spared Nerve Injury (SNI) model, which involves complete transections of the tibial and common peroneal nerve while sparing the sural and saphenous branches, mechanical hypers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 51 publications
(79 reference statements)
3
72
0
1
Order By: Relevance
“…Following sciatic nerve crush injury, these showed a significant delay in recovery of sensory functions, indicated by the Semmes–Weinstein monofilament test (Figure 1b). Most sensory recovery may have arisen from collateral sprouting, as the saphenous nerve remained uninjured and might have hyperinnervated the paw region, leading to the observed hypersensitivity (Duraku et al, 2012). We investigated recovery of motoric functions—measuring the footbase angle of mice in single‐frame motion analysis (SFMA) (Figure 1c) as a highly reproducible marker for functional muscle reinnervation (Fey, Schachner, & Irintchev, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Following sciatic nerve crush injury, these showed a significant delay in recovery of sensory functions, indicated by the Semmes–Weinstein monofilament test (Figure 1b). Most sensory recovery may have arisen from collateral sprouting, as the saphenous nerve remained uninjured and might have hyperinnervated the paw region, leading to the observed hypersensitivity (Duraku et al, 2012). We investigated recovery of motoric functions—measuring the footbase angle of mice in single‐frame motion analysis (SFMA) (Figure 1c) as a highly reproducible marker for functional muscle reinnervation (Fey, Schachner, & Irintchev, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…This is confirmed by the low levels of the compound in the plasma circulation-values below the concentration needed to block the rat CGRP1 receptor [11]. There is evidence that CGRP is present and is mediating nociceptive stimuli in the skin [31,44,56] and the sole of the foot (glabrous skin) of rats [12]. Intraplantar injection of CGRP can induce hypersensitivity in mice [50], and CGRP antagonists can block capsaicin-induced hypersensitivity when applied to the skin [48].…”
Section: Local Topical Application Of Bibn4096bs Reduces Wdr Neuronalmentioning
confidence: 86%
“…8 The sections were washed 5 times for 10 minutes in phosphate-buffered saline. Thereafter, the sections were pretreated with 30% hydrogen peroxide solution at room temperature for 10 minutes to ensure minimal background.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Duraku et al recently showed the importance of the distinction between subgroups of intra-epidermal nerve fibers (IENFs) by extensive collateral sprouting of peptidergic fibers from uninjured nerves, compared with the nonpeptidergic fibers following a spared nerve injury lesion. 8,9 However, regeneration of the different subgroups of IENFs has not yet been described following end-to-end reconstruction, which provides a better outcome compared with nerve graft repair. 45 It is also unclear if these fibers play a role in the pathogenesis of neuropathic pain similar to the spared nerve injury model.…”
mentioning
confidence: 99%